PENGARUH PUPUK ORGANIK KIRINYU UNTUK EFISIENSI PENGGUNAAN PUPUK UREA PADA PERTUMBUHAN TANAMAN PADI (Oryza sativa L.) - Tumewu, P.; Nangoi, Ronny; Walingkas, Stanley A. F.; Porong, Vikson J.; Tulungen, A. G.; Sumayku, Bertje R. A. (EUGENIA, 2019)
Conventional agriculture relies on the use of artificial chemical fertilizer, such as urea,during every planting season, causing a decrease in soil fertility. Unfertile land has a negative effect on rice production, putting strain on farmers.A replacement or complement for chemical fertilizers needs to be found; other than the negative long-term effects, increased demand for urea in the planting season can make it hard to find when farmers need it most. An organic alternative is kirinyu (Chromolaena odorata) which has high concentrations of nitrogen and also phosphorous, potassium, and other micronutrients. Kirinyu grows abundantly around rural farms and plantations and makes up a lot of local biomass. The aims of this research are to 1) Assess the interaction of kirinyu organic fertilizer dosage and urea dosage towards the growth of rice (Oryza sativa L.), and 2) determine the most efficient dosage of kirinyu and urea fertilizer for the best growth in rice. The research used a randomized block factorial design. The treatments were:Factor I (A) = Dosage of kirinyu organic fertilizer. A1 = 10 tons/ha, A2 = 20 tons/ha. Factor II (B) = Dosage of urea fertilizer. B1 = 50 kg/ha, B2 = 100 kg/ha, B3 = 100 kg/ha. Each treatment was replicated three times, resulting in 18 experiment plots. Variables observed were:height of plant and number of seedlings. Data was analyzed using analysis of variance and Least Significant Differences (LSD) at a test level of 5%. Results show that the combination of kirinyu organic fertilizer and urea fertilizer has a significant effect on plant height and number of rice seedlings.